Enhancing Social Relationship Skills through Social-Emotional Learning Using PjBL Mini-Drama at X-7 SMAN 17 Surabaya - Elvira Putri Amalia; Wijayadi; Nur Fitriah (PROCEEDING UMSURABAYA, 2026)
This study aims to improve the social relationship skills of Class X-7 students at SMAN 17 Surabaya by integrating Social-Emotional Learning (SEL) and Project-Based Learning (PjBL) through mini drama in narrative text in English learning. Involving 30 students, the research used a Classroom Action Research (CAR) design, including planning, implementation, observation, and reflection. Instruments included sociometric questionnaires (pre- and post-tests) and observation sheets evaluated by observers. Pre-test results showed most indicators were in the “Acceptable” to “Good” range, with the lowest score (63.34%) in students’ comfort involving unfamiliar peers. The intervention featured SEL videos, group discussions, script writing, peer feedback, and moral reflection. Observations showed active participation (90%), problem-solving (80%), and teamwork (90%). Post-test scores improved across all indicators, with “inviting unfamiliar peers” increasing to 78% and “group involvement” reaching 86.7%. These results align with Piaget’s and Vygotsky’s constructivist theories, SEL frameworks, and the effectiveness of PjBL and drama-based learning in developing communication, collaboration, empathy, conflict resolution, and advocacy. The study concludes that the PjBL Mini Drama model supported by SEL principles effectively enhances students’ social relationship skills in the English language learning context.